Global Play Football between Region, Nation, and the World in Latin American, African, and European History - Rinke, Stefan; Peters, Christina (Historamericana, 2022)
This book offers a collection of essays on the history of football by experts in Latin American, African, and European history and literary studies inspired by the new transnational historiography.